Glycan cross-feeding activities between bifidobacteria under in vitro conditions - Turroni, Francesca; Özcan, Ezgi; Milani, Christian; Mancabelli, Leonardo; Viappiani, Alice; van Sinderen, Douwe; Sela, David; Ventura, Marco (Frontiers in Microbiology, 2015)
Bifidobacteria colonize the gut of various mammals, including humans, where they may metabolize complex, diet- and host-derived carbohydrates. The glycan-associated metabolic features encoded by bifidobacteria are believed to be strongly influenced by cross-feeding activities due to the co-existence of strains with different glycan-degrading properties. In this study, we observed an enhanced growth yield of Bifidobacterium bifidum PRL2010 when co-cultivated with Bifidobacterium breve 12L, Bifidobacterium adolescentis 22L or Bifidobacterium thermophilum JCM1207. This enhanced growth phenomenon was confirmed by whole genome transcriptome analyses, which revealed co-cultivation-associated transcriptional induction of PRL2010 genes involved in carbohydrate metabolism, such as those encoding for carbohydrate transporters and associated energy production, and genes reuired for translation, ribosomal structure and biogenesis, thus supporting the idea that co-cultivation of certain bifidobacterial strains with B. bifidum PRL2010 causes enhanced metabolic activity, and consequently increased lactate and/or acetate production. Overall, these data suggest that PRL2010 cells benefit from the presence of other bifidobacterial strains.